Granulocytopenie - Čermák, Jaroslav (Vnitrni lekarstvi, 2018)
Granulocytopenia is defined as a decrease of peripheral blood granulocytes below lower limit of normal range. Patients with severe granulocytopenia - agranulocytosis exhibit < 0.5 × 109/l granulocytes in peipheral blood. Granulocytopenia may result from congenital or acquired defective production of granulocyte precursors or it may be a consequence of increased destruction of mature granulocytes, most frequently caused by immune mechanisms. Investigation of origin of granulocytopenia must be connected with exclusion of etiological agents causing secondary neutropenia (infections, autoimmune disorders, drugs, LGL syndrome). Patients with > 0.5 × 109/l of granulocytes usually do not exhibit clinical symptoms unless they do not suffer from a concomitant disease (especially immunodeficiency). Patients with severe granulocytopenia are indicated for supportive treatment and for administration of G-CSF. Children with severe congenital neutropenia (SCN) are at risk of later development of MDS or AML and are candidates for SCT when signs of disease progression appears. Key words: diagnosis - granulocytopenia - growth factors - pathogenesis - transplantation -treatment.
Keywords: Child; faktor stimulující kolonie granulocytů; Granulocyte Colony-Stimulating Factor; Autoimmune Diseases; Neutropenia; Agranulocytosis; neutropenie; granulocyty; autoimunitní nemoci; Humans; lidé; agranulocytóza; Leukocyte Count; počet leukocytů; dítě; Granulocytes; infekce; Infections